Crecimiento poblacional y cambios territoriales en el centro urbano de Salcedo, Puno - Ccama Condori, Hugo Anselmo (2021)
The urban expansion process generates negative effects on natural settings; this process is mainly caused by population growth that transforms natural territories for urban uses. The study aims to explain territorial changes as an effect of population growth in the urban center of Salcedo (Puno), understanding that population growth is one of the human actions that transforms natural territories and generates irreversible environmental effects. Methodologically, the study was based on the description of the current situation (diagnosis), for this the territorial analysis was carried out with the support of thematic mapping, referring to physical, spatial, and environmental aspects, to then process the information in the GIS software (ARC VIEW 3.2); subsequently, the perception of the population regarding the occupation of natural territories and deterioration of the environment was assessed. The results obtained report that the urban center of Salcedo experienced an accelerated population growth in the last decades, which directly influenced the increase of its urban area by 319 hectares; reducing natural rural areas to 302.4 hectares; This modification in the increase of its urban area has generated negative and adverse effects on the natural territory, occupying areas not suitable for urban uses, deterioration of the environment and pollution.